2006
DOI: 10.3147/jsfp.41.81
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of Koi Herpesvirus Disease in Rivers of Kanagawa Prefecture

Abstract: ABSTRACT-Mass mortality of carp Cyprinus carpio caused by koi herpesvirus disease (KHVD) occurred in seven rivers of Kanagawa Prefecture in 2004. Mortalities of KHVD peaked in May in four of the rivers (early outbreak group) and peaked in June in the other three rivers (late outbreak group). KHVD was first recognized at 15.5-18.5°C in the early outbreak group, and at 18.6-21.2°C in the late outbreak group. The temperature exceeded 15°C, which corresponds to the lowest temperature of the viral growth in cell cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…High seawater temperatures appear to be one of the potential factors likely to induce OsHV-1 infection. This hypothesis is consistent with observations on koi herpesvirus, for which temperatures between 18°C and 28°C favored the onset and severity of disease in fish (35)(36)(37)(38)(39)(40). Field surveys conducted in Japan showed that the lowest water temperature at which outbreaks occurred was 15.5°C to 16°C (36,39).…”
Section: Discussionsupporting
confidence: 90%
“…High seawater temperatures appear to be one of the potential factors likely to induce OsHV-1 infection. This hypothesis is consistent with observations on koi herpesvirus, for which temperatures between 18°C and 28°C favored the onset and severity of disease in fish (35)(36)(37)(38)(39)(40). Field surveys conducted in Japan showed that the lowest water temperature at which outbreaks occurred was 15.5°C to 16°C (36,39).…”
Section: Discussionsupporting
confidence: 90%
“…Experimentally, KHVD has been reproduced in temperatures ranging from 16 to 28°C (Gilad et al, 2003(Gilad et al, , 2004Yuasa, Ito, & Sano, 2008) and the lowest temperature associated with a CyHV-3 outbreak was 15.5°C in a field survey in Japan (Hara, Aikawa, Usui, & Nakanishi, 2006). Interestingly, CyHV-2 induces mortalities in goldfish at a slightly enlarged temperature range from 15 to 30°C (Ito & Maeno, 2014) suggesting a similar but adaptable temperature range in cyprinid herpesviruses.…”
Section: Effect Of Water Temperaturementioning
confidence: 87%
“…Comparable observations have been made for herpesviruses infecting vertebrates: for example, temperatures between 18°C and 28°C have been shown to favor the onset and the severity of Koi herpesvirus infection in fish (Gilad et al 2003;Hara et al 2006;Pokorova et al 2005;Saint-Hilaire et al 2005;Sano et al 2004;Yuasa et al 2008). However, it remains difficult to define a precise temperature threshold leading to enhanced OsHV-1 expression or mortality.…”
Section: Virus Diversitymentioning
confidence: 99%